2012
DOI: 10.3892/or.2012.1929
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the structural maintenance of chromosome 4 protein is associated with tumor de-differentiation, advanced stage and vascular invasion of primary liver cancer

Abstract: Structural maintenance of chromosome 4 (SMC4) is associated with tumorigenesis. The present study aimed at detecting SMC4 expression in primary liver cancer and its association with clinicopathological patient data. A total of 72 primary liver cancer tissues and 6 liver cell lines were assessed for expression of SMC4 mRNA and protein with qRT-PCR, western blotting and immunohistochemistry, respectively. SMC4 siRNAs were constructed to knockdown SMC4 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 30 publications
3
51
0
Order By: Relevance
“…Previous studies have shown that the expression of SMC4 mRNA and protein was highly upregulated in HCC tissues and cell lines. Levels of SMC4 protein were significantly associated with tumor size, differentiation, TNM stage, and vascular invasion of primary liver cancer [17]. From data presented on these 72 cases published previously, the 4 specimens selected in the current study are representative of the others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the expression of SMC4 mRNA and protein was highly upregulated in HCC tissues and cell lines. Levels of SMC4 protein were significantly associated with tumor size, differentiation, TNM stage, and vascular invasion of primary liver cancer [17]. From data presented on these 72 cases published previously, the 4 specimens selected in the current study are representative of the others.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that SMC4-Homo-830 (Table 2) greatly decreased SMC4 expression [17]. SMC4-Homo-830 was cloned into Pgpu/GFP/ Neo-shNC vector (GenePharma, Shanghai, China), and transfected into 97-H and HepG2, HCC cell lines.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…C0105; Beyotime Institute of Biotechnology) was obtained from Beyotime Institute of Biotechnology. An immunohistochemical assay was performed on formalin-fixed, paraffin-embedded HCC tissues using antibodies against UBE2A (27). Briefly, 4 µm slides were deparaffinized through a series of xylene baths and graded alcohols.…”
Section: Hematoxylyin and Eosin (Hande) And Immunohistochemistrymentioning
confidence: 99%
“…Other genes containing Tra2α/Tra2β target exons with G2 and S phase checkpoint that is essential in many cancer cells to prevent damaged chromosomes from entering mitosis [38] Vigilin (HDLBP) Represses proto-oncogene c-fms in breast cancer [43][44][45] KDM5A, KDM3A Histone methylases, erase epigenetic information, tumour promoters [46,47] NCOA Chromatin remodeling protein involved in breast cancer [48] ATRX Frequently mutated in paediatric cancer [49] SMC4 Key role in lung cancer, over-expressed in liver cancer [50,51] Nap1L1…”
Section: Tra2 Proteins Also Regulate Other Exons Potentially Importanmentioning
confidence: 99%